(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Introduzione: Il problema dell’estrema ingiustizia ne La Trilogia del ritorno – 2. La deferenza al diritto nella prospettiva di Uhlman – 3. Tortura: brevi riflessioni a partire dalle pagine de La trilogia. Law and extreme injustice. A reflection starting from Fred Uhlman’s pages ABSTRACT: This article adopts the perspective of the “Law and Literature” studies in order to focus on the terrible experience of the Holocaust that wracked Europe during the first half of the twentieth century. The theoretical and legal analysis is developed starting from the pages written by Fred Uhlman. Literature can help to move on to an in-depth debate that – from the issue of the violation of human rights – is to be carried out into the relationship between law and morality. The extreme injustice, the banality of evil and the radicalism of fascist ideologies represent the main themes this article starts from.